Obstructive Sleep Apnea Syndrome (OSAS): Continuous Positive Airway Pressure (CPAP) therapy and other positive-pressure devices - Sanna, Antonio (La Medicina del Lavoro, 2017)
The Obstructive Sleep Apnea Syndrome (OSAS) consists of recurring episodes of complete or partial obstruction of the pharynx. The application of a continuous positive pressure in the airways (CPAP) is the first therapeutic option that is found to ensure complete patency of the pharynx during sleep, avoiding apneas and hypopneas with resolution of the symptoms. More recently, other devices have been proposed as OSAS treatment. The auto-CPAP has a role in finding the therapeutic value of the CPAP pressure rather than in OSAS therapy. When apnea/hypopnea events are associated with other and/or predominant respiratory disorders like hypoventilation or Cheyne-Stokes breathing, the treatment of choice is the noninvasive ventilation with a double level of pressure support. Although it was proposed 35 years ago, the CPAP still represents the only effective therapy regardless of OSAS severity, as well as the treatment with the greatest evidence in terms of long-term benefits.